Student Participation in Preserving Non-Material Cultural Goods (Training and Practice : Journal of Educational Sciences, 2012)
The Republic of Croatia is a country which is rich in non-material cultural goods. Over the past few years, we have witnessed a growing awareness of a necessity for an efficient protection and conservation system of national cultural goods. Non-material cultural goods can be various forms of spiritual creation conveyed in a form of an oral history like languages, dialects, accents and toponymy. Encouraged by the importance of the Croatian non-material cultural goods, in the frame of faculty courses Slavonian Dialect and Native Idiom, we engaged students, future Masters of Teacher Education, in the process of preserving Croatian dialects, especially Slavonian dialect. The future teachers are the best protectors and promoters of the regional archaic vernaculars.